Li–Se batteries: Insights to the confined structure of selenium in hierarchical porous carbon and discharge mechanism in the carbonate electrolyte. (May 2022) - Lei, Youyi; Liang, Xinmiao; Yang, Li; Chen, Junfei; Qu, Luyao; Xu, Ke; Feng, Jiwen
Abstract: Confining selenium in porous carbon hosts is an effective strategy to improve the performance of Li–Se batteries. The structure of confined Se and the corresponding lithiation mechanism remain to be clarified yet. In this work, Se@CISC-58 composite material was prepared based on hierarchical porous carbon CISC-58 with same content of mesopores and micropores, and then used for cathode material of Li–Se batteries. The selenium loaded in Se@CISC-58 takes Sex chain structure rather than the cyclic Se8, as evidenced by both 77 Se MAS NMR and EPR experiments. In particular, the free radical signals in EPR changes adaptively with the discharge-charge cycling. Ex-stiu EPR and in-stiu 7 Li NMR techniques further confirmed the stepwise reaction mechanism of Sex chains in the carbonate-based electrolytes. To better understand the discharge process of selenium, NMR in combination with DFT calculations are utilized to assign the polyselenides engaged in discharge process. We have found that polyselenides represented by Li2 Se2 were generated during the discharge of selenium in the carbonate-based electrolytes. Graphical abstract: Image 1 Highlights: A hierarchical porous carbon CISC-58 with a ratio of micropore to mesopore volume 1:1 was synthesized. Se@CISC-58 with Se loading of 63% exhibits high reversible specific capacity of 420.5 mAh·g −1 after 1000 cycles at 1C. SsNMR and EPR confirmed the randomly coiled Sex chains in the confined nanopores. Ex-stiu EPR and NMR further confirmed the stepwise reaction mechanism of Sex chains in the carbonate-based electrolytes.